CUSTOMER SATISFACTION AND SERVICE QUALITY IN HEALTH CARE SERVICE DELIVERY INDUSTRY: A STUDY OF ANAMBRA STATE HEALTH INSURANCE AGENCY (UNIZIK Journal of Marketing, 2026)
This study, titled Customer Satisfaction and Service Quality in Healthcare Service Delivery Industry: A Study of Anambra State Health Insurance Agency (ASHIA), examined the effect of tangibles, reliability, and responsiveness on enrollee satisfaction. The problem arose from concerns that many healthcare providers under ASHIA fail to meet enrollees’ expectations regarding service delivery quality, particularly in areas of physical facilities, dependability, and responsiveness. A descriptive survey research design was adopted. The study population comprised 128,537 enrollees under ASHIA, from which a sample of 200 respondents was determined using Taro Yamane’s formula and proportionately allocated across selected hospitals in Awka and Onitsha. Data were collected through a structured questionnaire grounded on SERVQUAL dimensions, and validity was assured through factor analysis, while reliability was confirmed with Cronbach’s Alpha. Out of 200 questionnaires, 180 were properly completed and returned. Data analysis employed descriptive statistics, Pearson correlation, and multiple regression, with hypotheses tested at a 0.05 level of significance. The findings revealed that tangibles, reliability, and responsiveness significantly affect enrollee satisfaction, with tangibles exerting the strongest influence. The study concluded that improving these three dimensions is vital to enhancing satisfaction. Recommendations include upgrading facilities, sustaining reliable service delivery, enhancing staff responsiveness, and incorporating further research on assurance and empathy.